EXAMINING THE STRUCTURAL SIMILARITY OF CIVIL ENGINEERING SUBJECTS IN SHAHID CHAMRAN UNIVERSITY OF AHVAZ AND MATCHING THIS FIELD IN IRAN AND THE WORLD - S. Khademizadeh; R. Ghazavi; M. Aghaei; A. Mehri Dehno (آموزش مهندسی ایران)
The present research was conducted with the aim of investigating the structural similarity of civil engineering subjects in Shahid Chamran University of Ahvaz and its compatibility with Iran and the world. The research is considered as a type of scientometric applied studies. The statistical population is made up of researches related to the field of civil engineering in the Web of Science database. In order to check the thematic alignment, the clustering method was done with VOSviewer software. The index of structural similarity of subjects has also been used to determine the level of research alignment. Researchers have sought to search the subject areas of the Civil Engineering Department in Shahid Chamran University, Iran and the world. With the percentage of structural similarity, it was found that over time, the subjects of civil engineering in Shahid Chamran University have been aligned with Iran and the world, as well as Iran with the world, but the alignment of the subjects of Shahid Chamran University with Iran and the world is low. In order to increase the alignment of researches, forums should be established between specialists, researchers, experts, students and professors of civil engineering to share opinions and common thoughts. It also seems that monitoring the research trends and their similarity with the world’s top research institutes puts a new perspective in front of research policy makers and is basically effective in finding the strengths and weaknesses of research approaches and future policies